Correlation of Depression and Nightmares in Young Medical Students: Correlation of Depression and Nightmares - Yousaf, Kanza; Pasha, Hafiza Hina (Pakistan Journal of Health Sciences, 2025)
Consistent dream sequences that appear genuine and become more upsetting as they progress are known as nightmares. A prevalent condition that significantly impairs psychosocial performance and lowers quality of life is major depression. Insomnia and nightmares independently but additionally have an impact on the exacerbation of depression. Objectives: To find the correlation between depression and nightmares in young medical students. Methods: A cross-sectional study was carried out from September 2021 to June 2022, involving 350 medical students aged 18 to 30, distributed across all academic years. The symptoms of depression were measured and assessed using the CES-D scale, while nightmares were evaluated by using a validated sleep 50 questionnaire. Data were analyzed in SPSS version 27.0. Results: A total of 350 medical students (49.1% male and 50.9% female), with most aged 19 to 23 years, 91.4%, and single, 97.7%. The mean CES-D score was 23.0 ± 12.42, higher in females 24.8% than in males 21.0. Severe depression was more common in females 44.9%) and first-year students 58.6%. Frequency of nightmares was reported by 23.9%, and the depressed feelings and the frequency of nightmares are significantly correlated (P=0.019). Pearson correlation analysis shows a substantial correlation between the frequency of nightmares and depressive moods. (P≤0.01). Conclusion: The study concluded a significant association between depression symptoms and nightmares, particularly in females and younger medical students. Academic and social factors significantly influence depression symptoms.